2014
DOI: 10.5376/ija.2014.04.0023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Identification of Bacteria Isolated from Seaweed <i>Gracillaria verrucosa</i> (Linn., 1758) Infected by Ice-ice

Abstract: Ice-ice disease in cultivated algae occurs due to pathogenic bacterial infections. Generally, ice-ice disease is characterized by whitening of the branches and initiated with the color changes of the thalli becomes transparent. This study was aimed to isolate and identify bacteria on seaweed Gracilaria verrucosa infected by ice-ice. Isolated bacteria was inoculated in Tryptic Soy Agar (TSA) and Thiosulphate Citrate Bile Sucrose (TCBS). Morphological and biochemical characterization of the bacterial isolates re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The agarolytic activity exhibited by G. chinensis indicated that it is an ice-ice disease-causing bacterium. 1982;Largo et al 1995b;Lavilla-Pitogo 1992;Mahmud et al 2007Mahmud et al , 2008Nasmia et al 2014;Stabili et al 2017;Vairappan et al 2008). V. brasiliensis and V. harveyi were present in nutrient-enriched and untreated K. striatus on…”
Section: Discussionmentioning
confidence: 99%
“…The agarolytic activity exhibited by G. chinensis indicated that it is an ice-ice disease-causing bacterium. 1982;Largo et al 1995b;Lavilla-Pitogo 1992;Mahmud et al 2007Mahmud et al , 2008Nasmia et al 2014;Stabili et al 2017;Vairappan et al 2008). V. brasiliensis and V. harveyi were present in nutrient-enriched and untreated K. striatus on…”
Section: Discussionmentioning
confidence: 99%
“…17,19 There are a small number of publications reporting similar disease signs as IID in cultivated Gracilaria spp. in Indonesia and the Philippines, [50][51][52] Notes: Descriptions of IID signs from publications in languages other than English have been translated (original language in parentheses). References which have not been subjected to peer review are marked with an asterisk.…”
Section: Suscep Tib Ilit Yofeucheumatoid Ta X Atoiidmentioning
confidence: 99%
“…Seaweed also has various secondary metabolite compounds that have potential in the treatment of various diseases caused by pathogenic microbes. The use of seaweed bioactive compounds has begun to be developed to replace the use of synthetic chemical raw materials, which are harmful to humans and the environment (Nasmia, 2014). Currently, seaweed processing is carried out in the industry.…”
Section: Introductionmentioning
confidence: 99%